Voice Controlled Smart Helmet - Prashanna Rangan, R.; Sangameshwaran, M.; Poovendan, V.; Pavanpranesh, G.; Naveen, C. (Asian Review of Mechanical Engineering, 2018)
A helmet is a kind of safety gear, which is used by many motorists around the world. It protects the head from the impacts during accidents. According to a survey, many people nearly half die due to the time lag in the treatment that is provided to them after the accident. The reason behind this delay may be due to lack of passage of information, traffic issues etc. It came up with this idea of giving the information about accident as soon as possible and in time. Death due to road accidents can be minimized, if treatment is provided at proper time. The major problem is the lack of passage of information regarding the accidents. Because after all, time matters a lot, if everything is done in time, at least we can half the lives that are lost due to the bike accidents. This work aims in passing the information regarding the accidents and the exact location to the relatives of the victim and also to the nearby hospitals with the aid of GPS and IoT. The system also consists of voice module to control the visor, turn indication, headlights, horn, and also the ignition system, the user is given much more options to control the vehicle rather than getting deviated from driving. Since the user uses voice controls to do the activities, he/she will stay awake throughout the ride.